A STUDY ON THE SECOND YEAR STUDENTS SPEAKING ABILITY IN EXPRESSING INVITATION AT SMA ISLAM AS-SHOFA PEKANBARU - Putri, Risti Ayu; Aruan, Rumiri; Novitri, Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was a study on the speaking ability in expressing invitation of the second year students of SMA As-Shofa Islam Pekanbaru.The aim of this research was to know about the second year students speaking ability in expressing invitation at SMA Islam As-Shofa Pekanbaru. The population of this research was the second year students of SMA Islam As-Shofa Pekanbaru that divided into 4 classes, with total 91 students. The sample of this research was class X1 MIA 2, with total 22 students.The instrument of this research was expressing invitation in role play. In conducting this research, a set of expressing invitation in role play card was used to know students’ speaking ability. To get the quantitative data in this research, the three raters were involved to give the scores of students speaking ability. The mean score of students’ ability in speaking from the first rater was 79.2, (good level). The second rater’s mean score was 78.8, (good level). Lastly, from the third rater was 80 (good level). The research finding also shows that students got the highest mean score in terms vocabulary (4.1) and got the lowest mean score in terms of pronunciation (3.7). In conclusion, from the three raters in five aspects of speaking ability, the average of speaking ability of students at the second year of SMA Islam As-shofa Pekanbaru were 79.3 (good level).Keywords : descriptive research, students’ speaking ability